No lessons learned : the making of Curb Your Enthusiasm as told by Larry David and the cast and crew - Ali, Lorraine (Black Dog & Leventhal Publishers : HBO Original : Melcher Media, 2025)
"This fully authorized celebration of the Emmy award-winning, genre-busting, longest-running, HBO Original comedy Curb Your Enthusiasm is told by Larry David and the show's creators, cast, crew, and celebrity guests. A must-have for fans of the series. The official companion book from the team behind the HBO Original series Curb Your Enthusiasm reveals all the magic, mayhem, and creative genius that went into making one of the most influential and funniest shows in television history. Running a record 12 seasons, 24 years, 120 episodes and drawing millions of die-hard fans, Curb has established itself in the entertainment pantheon as nothing less than a cultural touchstone. Its iconic lines, comedic bits, and famously awkward scenarios live on in our collective consciousness long after the finale, as does our undying affection for the phenomenal cast, including Larry David, Jeff Garlin, Susie Essman, J.B. Smoove, Cheryl Hines, Ted Danson, the late Richard Lewis, and Bob Einstein. No Lessons Learned: The Making of Curb Your Enthusiasm covers it all through first-person interviews with the principal cast and crew, as well as select guest stars, episode guides, never-before-seen and behind-the-scenes photographs, archival material including annotated scripts, storyboards and sketches, Larry David's legendary outlines written on legal pads, and much, much more. Additional special features include: A glossary of Larry David-isms including stop-and-chat, chat-and-cut, pants tent, pig parker, and more -- Leon Black's Guide to Romance -- A map of LA featuring key locations both real and fictional -- Sartorial stylings of Susie Greene -- Memorable cameos."--Publisher.